Suku Dayak: Mengenal Tradisi Adat dan Kehidupan Masyarakatnya - Oktaviani, Dwi; Kurnia, Heri (Jurnal Ilmu Sosial dan Budaya Indonesia, 2023)
This research is a literature study which aims to provide an in-depth understanding of the traditional and cultural traditions of the Dayak people, an indigenous ethnic group in Central Kalimantan, Indonesia. The Dayak tribe is known to have rich cultural diversity, including in terms of belief systems, traditional ceremonies, tiwah ceremonies, and their unique way of life. This literature study will collect and analyze various literary sources, including books, journal articles, and official documents that are relevant to the traditional traditions and culture of the Dayak tribe. The collected data will be analyzed to identify patterns, developments and important aspects of Dayak culture, as well as how their culture has interacted with modernization and social change. It is hoped that the results of this literature study will provide a deeper understanding of the cultural diversity of the Dayak tribe.